IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPAS PESERTA DIDIK KELAS IV SD NEGERI 02 MOJOREJO - Fitrianingsih, Wulan Indah; Wardani, Henny Kusuma; Karjanto, Singgih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to study science and science learning outcomes for class IV students at SDN 02 Mojorejo, Madiun City by applying the make a match cooperative learning model. This type of research is Classroom Action Research (PTK). The approach used in this Classroom Action Research is Qualitative Descriptive. Observation data collection techniques were used to obtain data on student learning activity, while tests were used to obtain data on learning outcomes for class IV students at SDN 02 Mojorejo, Madiun City. The data obtained was analyzed quantitatively using percentage techniques. The results of the research showed that there was an increase in students' science learning outcomes, in the pre-cycle science students' learning outcomes only reached 39%, then student learning outcomes in cycle I were 48%, and student learning outcomes increased to 90% in cycle II. So overall student learning outcomes in class IV science subjects from pre-cycle, cycle I and cycle II are 51%. This shows that students' level of classical completion has increased and has achieved expectations. Based on the results of this research, it can be concluded that the application of the make a match learning model is able to improve the science and science learning outcomes of class IV students at SDN 02 Mojorejo for the 2023/2024 academic year.